Development & application of a molecular toolbox for the unconventional yeast Candida intermedia - Larsson, Adam (My University, 2017)
Over the last years there have been extensive attempts at replacing fossil fuels with the more sustainable option bioethanol. Traditionally bioethanol is produced using Saccharomyces cerevisiae to ferment glucose from crops such as sugar cane, but this is unsustainable as it doesn’t utilize the whole biomass and the resource generationcompeteswithfoodproduction. Insearchofmoresustainablesubstrates the scientiﬁc community has turned to more unconventional microorganisms as S. cerevisiae is less adept at using sugars other than glucose. In this project an interesting Candida intermedia strain, named C11, was studied. The strain has exhibited interesting traits for utilization of lactose/galactose and xylose. Three aldose reductase genes, XYL1, XYL1_2 & XYL1_3, have been identiﬁed to be of especial interest for xylose metabolism. XYL1_2 also seems to be of interest for lactose/galactose metabolism as the gene is located in a novel galactose gene cluster. The aim of this project was thus to study the physiological roles of the three aldose reductases Xyl1p, Xyl1_2p & Xyl1_3p. The expression levels of the three aldose reductase genes were measured in cells grown in glucose, lactose & xylose to ﬁnd hints as to the role of the enzymes. XYL1 was found to be upregulated during growth on xylose, whereas XYL1_2 was upregulated in lactose containing growth medium. This suggests Xyl1p’s role to be that of a xylose reductase used in xylose metabolism. It also suggests that Xyl1_2p isimportantforlactose/galactoseutilization. Tofurtherstudythephysiologicalrole of the aldose reductases the goal was to delete them from the genome to obtain a phenotype indicating the role of the enzymes. C. intermedia stronglyfavorsnon-homologousendjoining(NHEJ)overhomologous recombination(HR)makingtargetedgenedeletionsnear-impossible(<1%oftransformed cells). For this reason genetic tools were developed, at great success, for C. intermedia C11 to facilitate gene deletions with a high gene target eﬃciency. The best obtained deletion protocol was based on an unconventional method of using a split marker deletion cassette. The resulting protocol is quick and provides a gene targeting eﬃciency of up to 67 %. The deletion protocol was applied in the deletion of aldose reductase gene XYL1_2. The deletion strain did however not produce a visible phenotype when grown on galactose. During the project suggestions as to the metabolic role of Xyl1p & Xyl1_2p were found. A very eﬃcient gene deletion protocol was developed with a gene targeting eﬃciency of 67 % and it was applied to delete XYL1_2. However, more work is needed to fully evaluate the three aldose reductases and the novel galactose gene cluster, for example by producing more deletion strains.
Keywords: Biologiska vetenskaper; Industriell bioteknik; Biological Sciences; Industrial Biotechnology